The Influence of Tiktok Shop on Increasing Customer Purchase Intention Of Beauty Products (Journal of Business and Management, 2022)
Abstract. TikTok Shop is a yellow shopping cart in the lower left TikTok homepage. Due to the pandemic, selling products is hard so the purchase intention is lower and business owners are losing profit. TikTok in rapidly growing users is an opportunity to increase purchase intention. Besides, TikTok Shop also has disadvantages based on findings in customer reviews in the TikTok Shop and other media. Although TikTok is a popular social media platform, this does not guarantee that TikTok Shop will increase purchase intent. This study aims to assess the effect of TikTok Shop towards purchase intention and gives recommendations to beauty product sellers on how to increase the purchase intention. This study uses a quantitative approach towards 222 peoples who purchase beauty products through the Tiktok Shop. The researcher uses descriptive statistics and PLS- SEM to analyze the survey result. The result indicates that number of followers, eWOM, and store reviews positively affect trustworthiness. Trustworthiness and perceived value positively affect purchase intention on beauty products in TikTok Shop. The implications of the study's empirical findings is to give insight for beauty product sellers to increase profits by conducting marketing strategies for promoting beauty products in Indonesia.Keywords: Beauty Product, Perceived Value , Purchase Intention, TikTok Shop, Trustworthiness